Geospatial information management between hydrography and the law of the sea: A milestone opportunity for their further integration - Tani, Ilaria (The International Hydrographic Review, 2025)
These past few years have marked the beginning of a revived surge of interest worldwide for the topic of marine geospatial information management, which is reflected in the work of the International Hydrographic Organization and United Nations relevant bodies. Building on this momentum, this contribution firstly introduces a milestone initiative on marine geospatial data recently launched by the United Nations General Assembly. Secondly, it addresses the significance of marine geospatial data collection, storage, and dissemination for the law of the sea. Finally, the role of hydrographic offices is emphasized in the challenge of moving from local to global in the management of marine geospatial data, focusing on the experience of the Italian Navy Hydrographic Office.